Proanthocyanidins (condensed tannins) and the use of leaves from Sesbania sesban and Sesbania goetzei as protein supplements - Weigand, R.O.; Reed, J.D.; Said, A.N.; Umunna, N.N. (Elsevier, 1995)
Three accessions of Sesbania sesban (10865, 15019 and 15036) and one accession of Sesbania goetzei (15007) were used as protein supplements for rams fed maize (Zea mays) stover in a growth trial and a digestion trial which investigated the effects of proanthocyanidins (PAs) on protein digestion. Levels of soluble and insoluble PAs were highest, in accessions 15036 and 15007, inter-mediate in 15019 and lowest in 10865. In a 70 days growth trial, 60 rams were fed these accessions of sesbania which provided three levels of crude protein (25, 50, and75 g day-1). Intakes of maize stover by rams fed accessions 10865 and 15019 were significantly higher (P<0.05) than rams fed 15036 and 15007. Rate of gain for rams fed accessions 10865 and 15019 were significantly higher (P<0.01) than for rams fed accessions 15036 and 15007. In the digestion trial, 12 rams were fed the four sesbania accessions and three levels of sesbania in a replicated 3 X 3 Latin square design. Intake of maize stover decreased as the level of sesbania increased for rams fed accessions 15036 and 15007. High levels of PAs depressed the digestibility of neutral-detergent fiber (NDF) which decreased the intake of maize stover. The digestion coefficients for acid-detergent lignin (ADL) were negative for accessions 15019, 15036, and 15007. The digestion coefficients for neutral-detergent insoluble N (NDIN) were negative for rams fed accessions 15036 and 15007. Negative digestion coefficients resulted from more fecal excretion of these fractions than were consumed. PAs may form detergent insoluble complexes in the digestive tract. Rams fed accessions 15036 and 15007 had the highest excretion of total fecal N and fecal NDIN and the lowest urinary N. Rams fed accession 10865 had the highest urinary N excretion and the lowest excretion of total fecal N and fecal NDIN. Rams fed accession 15019 had the highest N retention. The intermediate level of PAs in accession 15019 may have beneficial effects on protein digestion. High levels of PAs in accessions 15036 and 15007 may have detrimental effects. Forage N had nutritionally non-uniform digestion in accessions 15019, 15036 , and 15007. Fecal excretion of NDIN was significantly correlated to intake of soluble PAs (r=0.941) and insoluble PAs (r=0.789). The formation of detergent insoluble complexes in the digestive tract violate principles of detergent analysis but this deviation from ideal behavior can be used to determine the effects of PAs on protein digestion.